ANALISIS TINGKAT KEBISINGAN (NOISE) PADA AREA FATTY ACID PHASE 1 DI PT PERMATA HIJAU PALM OLEO KIM II MABAR - Sumando Sinaga; Masdania Zuhrira Sr; Rizkha Rida (Journal of Innovation Research and Knowledge, 2025)
Noise is an unwanted sound or sound that can disrupt health, comfort and cause deafness. PT. Permata Hijau Palm Oleo KIM II Mabar is a palm oil derivative processing factory that produces fatty acids. In the processing process PT. Permata Hijau Palm Oleo KIM II Mabar uses machines that cause interference. This research aims to determine the level of existing disturbances and disturbances as well as proposals for controlling disturbances on the production floor. The data collection method is observational using the equivalent disturbance level (Leq) calculation method. Data collection was carried out at 16 points on the production floor. The research results and interference distribution patterns show high levels of interference in several areas reaching 88.18 dB. The permitted threshold value based on the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number PER.13/MEN/X/2011 is 85 dB. Therefore, we need to control disturbances to prevent and reduce the consequences of these disturbances.